The Effect of Garlicing with Decorated Binahong Leaves (Anredera Cordifolia) on Saliva Ph - Desih Welliam; Mery Erfiani; Kelfin, Kelfin (Jurnal EduHealth, 2025)
Saliva is formed from secretion gland saliva on the oral mucosa , with production daily around 700 ml. Normal saliva pH is around 6-7, with pH changes are influenced by taste stimulation . Binahong ( Anredera cordifolia ) is plants that are capable growing in the plains low and high , all part plant binahong Can utilized , but the most common used in herbal medicine is the leaves Because contain compound chemistry like saponins , flavonoids, polyphenols , and triterpenoids . Purpose from study This is For know influence gargle stew leaf binahong ( Anredera cordifolia ) on saliva pH student health tooth class of 2023. Method Study used​ is quasi -experimental with design pre and post test group design . Study This get sig . value of 0.00 so (a < 0.05) then There is influence gargle stew leaf binahong ( Anredera cordifolia ) on saliva pH student health tooth class of 2023.